MANAJEMEN EKSTRAKURIKULER TEATER DALAM PENGUATAN KARAKTER SISWA SMP - Dyah Putri Ekowati; Ahmad Thohirin; Suyitno Suyitno (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research is motivated by the importance of extracurricular activities as a vehicle for developing non-academic potential and building student character. One activity that significantly contributes to character development is the theater extracurricular activity. This study aims to describe the management of theater extracurricular activities in developing student character at SMP Negeri 2 Wonorejo. The study used a qualitative approach with a case study approach. Data sources included the principal, vice principal for student affairs, theater extracurricular instructor, and students participating in theater activities. Data collection techniques were conducted through observation, in-depth interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. While data validity was obtained through triangulation of sources and techniques. The results show that the management of theater extracurricular activities at SMP Negeri 2 Wonorejo includes structured program planning, activity implementation oriented towards creative and collaborative processes, and evaluation that emphasizes the development of student attitudes and skills. Theater activities contribute to the development of students' character traits of discipline, responsibility, cooperation, self-confidence, and creativity. Thus, extracurricular theater serves not only as a means of developing artistic talent but also as a medium for character education in schools. ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya kegiatan ekstrakurikuler sebagai wahana pengembangan potensi nonakademik dan pembentukan karakter peserta didik. Salah satu kegiatan yang memiliki kontribusi signifikan dalam pengembangan karakter adalah ekstrakurikuler teater. Penelitian ini bertujuan untuk mendeskripsikan pengelolaan kegiatan ekstrakurikuler teater dalam pengembangan karakter siswa di SMP Negeri 2 Wonorejo. Penelitian menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Sumber data penelitian meliputi kepala sekolah, wakil kepala sekolah bidang kesiswaan, pembina ekstrakurikuler teater, dan siswa yang mengikuti kegiatan teater. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi. Analisis data dilakukan dengan tahapan reduksi data, penyajian data, dan penarikan kesimpulan, sedangkan keabsahan data diperoleh melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa pengelolaan ekstrakurikuler teater di SMP Negeri 2 Wonorejo meliputi perencanaan program yang terstruktur, pelaksanaan kegiatan yang berorientasi pada proses kreatif dan kolaboratif, serta evaluasi yang menekankan pada perkembangan sikap dan keterampilan siswa. Kegiatan teater berkontribusi dalam pengembangan karakter disiplin, tanggung jawab, kerja sama, percaya diri, dan kreativitas siswa. Dengan demikian, ekstrakurikuler teater tidak hanya berfungsi sebagai sarana pengembangan bakat seni, tetapi juga sebagai media pendidikan karakter di sekolah.